Comparative Study of Different Image Enhancement Techniques - Garg, Saruchi; Lal, Madan (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
The main purpose of image enhancement is to bring out detail that is hidden in an image or to increase contrast in a low contrast image. Image enhancement techniques provide a multitude of choices for improving the visual quality of images. Appropriate choice of such techniques is greatly influenced by the imaging modality, task at hand and viewing conditions. This paper analyses the performance of some of existing image enhancement algorithms. The performance of algorithms are evaluatedÂ both qualitatively and quantitatively.